Cladocerans and copepods captured linked with postlarvae of penaeid shrimps in southern Sinaloa, Mexico - Felix-Ortiz, José Adán; Arroyo-Bustos, Gloria Ana María; Bautista Peinado, Jesús Saúl; Hernández-Martínez, Alfonso; Arzola Gonzalez, Juan Francisco (Ecosistemas y Recursos Agropecuarios, 2021)
The accompanying microcrustaceans of penaeid postlarvae were analyzed between the mouth of the Presidio River and marine area (southern Sinaloa, Mexico). The samplings were at high tides (May to October 2017). A plankton net at a depth of 1 m. The trawls were every 2 h for 24 h. The water temperatura (25 to 34 ◦C) and salinity (32 to 35 ups). The taxonomic composition of postlarvae: Penaeus vannamei, P. stylirostris, P. californiensis and P. brevirostris. Cladocerans: Penilia sp, Evadne sp and Pseudoevadne sp. Copepods: Labidocera sp, Subeucalanus sp, Pseudocalanus sp, Centropages sp1 and Centropages sp2. The highest occurrence frequency Labidocera sp and relative abundance Penilia sp. The microcrustaceans on averange measured less than 11 mm, the largest postlarvae and smallest cladocerans. The cladoceran Penilia sp and copepod Labidocera sp and the P. vannamei, P. californiensis and P. brevirostris postlarvae dominated.